2011
DOI: 10.1016/j.joca.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risk factors for osteoarthritis of the knee: a meta-analysis

Abstract: Some occupational activities increase the risk of knee OA, although the influences of publication bias and heterogeneity are important limitations of this study. Prospective studies would greatly improve the evidence base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
102
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 71 publications
9
102
0
2
Order By: Relevance
“…Our study also demonstrated that symptomatic knee OA was more common among persons living in rural areas compared with urban areas in China; this finding was consistent with those of previous studies SYMPTOMATIC KNEE OSTEOARTHRITIS IN CHINA 651 (13,14). Given that residents living in less-developed or rural areas often have limited resources, including fewer clinics, safe options for public transportation, community centers, and safe places to exercise, as well as poorly kept sidewalks and less access to safe streets (28)(29)(30), studies of the impact of symptomatic knee OA on the residents in these communities are urgently needed. We demonstrated an apparent geographic variation in the prevalence of symptomatic knee OA in China.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also demonstrated that symptomatic knee OA was more common among persons living in rural areas compared with urban areas in China; this finding was consistent with those of previous studies SYMPTOMATIC KNEE OSTEOARTHRITIS IN CHINA 651 (13,14). Given that residents living in less-developed or rural areas often have limited resources, including fewer clinics, safe options for public transportation, community centers, and safe places to exercise, as well as poorly kept sidewalks and less access to safe streets (28)(29)(30), studies of the impact of symptomatic knee OA on the residents in these communities are urgently needed. We demonstrated an apparent geographic variation in the prevalence of symptomatic knee OA in China.…”
Section: Discussionsupporting
confidence: 91%
“…6,7 Since we began our study, two other groups have published reviews on this topic. 47,48 Fransen and colleagues, 47 who examined the role of occupational factors in hip and knee pain, reported a significant association between heavy lifting, kneeling or squatting, and symptomatic knee OA. They identified eight new publications on knee OA since the review by Jensen and colleagues, 6 five of which were also included in our review (the other three failed to fit our inclusion criteria for radiographically or MRIconfirmed signs of knee OA).…”
Section: Discussionmentioning
confidence: 99%
“…Although Fransen and colleagues also examined occupational tasks individually, they did not examine the risks separately for men and women. In a second review, McWilliams and colleagues 48 performed a meta-analysis on 51 observational studies to assess the relationships between occupational factors (''heavy work,'' ''kneeling activity,'' elite sports participation, job titles) and knee OA. Their meta-analysis found a statistically significant association between occupational physical loading and knee OA; however, they did not assess the methodological quality of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Palmer concluded that there is reasonably good evidence to connect work activity and knee OA and -more specifically -that this evidence is stronger with regard to squatting / kneeling, lifting and physical workload, somewhat weaker for climbing and somewhat against an important effect caused by standing or walking [2]. McWilliams et al conducted a meta-analysis on the same topic, highlighting that occupational activities such as kneeling, squatting, lifting/carrying, climbing stairs and knee bending/straining, gave positive risks for knee OA [7]. In contrast, the analyses also pointed out that standing work was not a risk factors for knee OA.…”
Section: Discussionmentioning
confidence: 99%